2019
DOI: 10.2131/jts.44.601
|View full text |Cite
|
Sign up to set email alerts
|

Dose- and time-dependent changes in blood and adrenal levels of multiple steroids in rats after administration of ketoconazole with or without ACTH

Abstract: To verify simultaneous measurement of blood levels of adrenal steroids as a tool to evaluate drug effects on adrenal steroidogenesis, dose-and time-dependent changes in blood levels of corticosterone and its precursors (pregnenolone, progesterone and deoxycorticosterone), as well as their relationship with the pathological changes in the adrenal gland, were examined in rats dosed with ketoconazole (KET). Also examined were whether effects on adrenal steroidogenesis that were not obvious in the blood steroid le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Moreover, this enzyme plays a critical role in corticosteroid synthesis and metabolism. Therefore, beside antifungal potential, it is one of the few available remedies for Cushing's syndrome . Although this drug is effective in decreasing cortisol and reducing the clinical effects of Cushing's syndrome, it is life‐threatening due to the risk of severe hepatotoxicity …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this enzyme plays a critical role in corticosteroid synthesis and metabolism. Therefore, beside antifungal potential, it is one of the few available remedies for Cushing's syndrome . Although this drug is effective in decreasing cortisol and reducing the clinical effects of Cushing's syndrome, it is life‐threatening due to the risk of severe hepatotoxicity …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, beside antifungal potential, it is one of the few available remedies for Cushing's syndrome. 7 Although this drug is effective in decreasing cortisol and reducing the clinical effects of Cushing's syndrome, it is life-threatening due to the risk of severe hepatotoxicity. 8 Moreover, it has been reported that this antifungal agent is able to induce a variety of heart function side effects, such as long-QT syndrome 9 and ventricular arrhythmias.…”
mentioning
confidence: 99%